(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2011)
Tho Powor of Focu - Nokia completely and sharply focuaaod on mobllo phonos. Being ahead of the curve was anothor component of Nokia’s strategy In India, as thoy had lnvosted beforo everybody else In the brand, in tho pooplo, and most Importantly, In distribution. Nokia lnvostod moro than 1 billion In India which proves fts focus on omorglng markets too. Tho Distribution Edge- Investments In people is difficult to Judge, overy company claims to have the best talon! In tho business. But whon It comes to distribution Nokia takes tho lead. .Nokia started distributing Its phonos through a partnership with HCL (formerly Hindustan Computors Ltd)) which had already built an oxtonslvo notwork for Its own products. Recently, Nokia has dooldod to own distribution efforts and has opened up storos In various cities.